Structural, optical, and antibacterial efficacy of pure and zinc-doped copper oxide against Pathogenic bacteria - Khalid, A.; Ahmad, P.; Alharthi, A. I.; Muhammad, S.; Khandaker, Mayeen Uddin *; Rehman, M.; Faruque, M. R. I.; Din, I. U.; Alotaibi, M. A.; Alzimami, K.; Bradley, D.A. * (MDPI, 2021)
Copper oxide and Zinc (Zn)-doped Copper oxide nanostructures (CuO-NSs) are successfully synthesized by using a hydrothermal technique. The as-obtained pure and Zn-doped CuONSs were tested to study the effect of doping in CuO on structural, optical, and antibacterial properties. The band gap of the nanostructures is calculated by using the Tauc plot. Our results have shown that the band gap of CuO reduces with the addition of Zinc. Optimization of processing conditions and concentration of precursors leads to the formation of pine needles and sea urchinlike nanostructures. The antibacterial properties of obtained Zn-doped CuO-NSs are observed against Gram-negative (Pseudomonas aeruginosa, Klebsiella pneumonia, Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria via the agar well diffusion method. Zn doped s are found to have more effective bacterial resistance than pure CuO. The improved antibacterial activity is attributed to the reactive oxygen species (ROS) generation.